Membrane-damaging and cytotoxic sphingomyelinases and phospholipases - Flores Díaz, Marietta (2015)
This chapter presents an overview of the classification, structure, and main physiopathological activities of bacterial sphingomyelinases and phospholipases, providing examples of their roles as virulence factors in several human and animal diseases. Bacterial sphingomyelinases (SMases) and phospholipases (PLases) constitute a heterogeneous group of surface-associated or secreted esterases produced by a variety of intracellular and extracellular pathogens. These enzymes might favor in different ways tissue colonization establishment and progression of the infection, or evasion of the immune response. In several cases, mutant bacterial strains lacking a sphingomyelinase or a phospholipase encoding gene have impaired virulence in experimental animals, demonstrating the role of these enzymes in pathogenicity. However, PLases contribute also to other aspects of bacterial lifestyle, including survival in different environments, and competition with other microorganisms; thus, the multifunctional nature of these enzymes reflects the remarkable adaptability of some bacteria.